FAKTOR PENGHAMBAT PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT PEMBANGUNAN INFRASTRUKTUR SOSIAL EKONOMI WILAYAH DI KABUPATEN TABALONG KALIMANTAN SELATAN - Erwan Pemkab Tabalong (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2017)
National program development of socio-economic infrastructure is a program that aims to accelerate the economic development of rural communities based on local resources, reduction of disparities between regions, reducing poverty, improving the management of local governments at the district, sub-district and village as well as the strengthening of local institutions at the village level. The purpose of this study are: (1) How is the effectiveness of implementation of PNPM-PISEW program in strategic area of Tabalong; (2) Finding the factors that supported and obstacles of the implementation of the PNPM-PISEW, and (3) Formulate an alternative model that can be applied to community empowerment in Tabalong.This research done by qualitative approach by using formative evaluation to measure the effectiveness of the implementation of PNPM-PISEW program. The data collected through interview and documentation. Data analysis by descriptive analysis.The results of research shown that PNPM-PISEW implementation is not optimum yet. So this policy outcome is moderate effectively. Some factors may be identified as supporting like as society obedience; local government support and public participatory, so the obstacle factors like as lack of sinergisity and lack of individual and social capacity of target group.The positive outcome of the PNPM-PISEW in Strategic Areas Tabalong are the increase of income, increase of employment opportunities, and increase the capacity of the local government.